منهج ابن كثير السنني في تفسيره وأثره في توجهات أهل الحديث (المنطقة الغربية- ليبيا- نموذجا) - Mahmud Mokhtar Etbib
This thesis is an attemp of studying the impact and the methodology of Al-Hafiz Ibn Kathir As-Sunniyy in Libya environment (Western region of Tripoli as a case study). Ibn Kathir during his life time was able to contribute towards the development of many scholars, students, authors and researchers. This work aims at study the Sunnatic approach of Ibn Kathir in addressing the theological and Judicial issues in his book of tafsir and other works of him. He added an addendum of Hakim to Mu'atta. Also, both various old and new books of tafsir will be adequately studied in this work, such books like; tafsir at-Tabari, Ibn Taimiyyah among the olden, Jawhariyy of Tantawi, Muhammad Rushd and As-Sa'diyy among the newest and their current methods of tafsir respectively. Studied here as well, the approach of the scholars of Hadith in Western part of Tripoli presently and in the past in relation to Maliki's school of law. The history of Tripoli, its mosques, universities and the activities of those who opposed Sunnah is intended to be traced and studied accordingly. The aim of this work is to make known how education activities were established and its development in Andalus and how its environment affected the thinking of Ibn Kathir, in order to relate it to the old method with the new one. Likewise to study the method of Ibn Kathir in using an hadith and in giving preference to one hadith over another while discussing the issues of 'Aqidah (theology), 'Ilm Kalam and Islamic jurisprudence. The impact of 1bn Kathir on his contemporary scholars towards following Sunnah will be also explained in detail. At the end of this work, the following objectives are aimed to attain; to discuss the historical background of Education and knowledge in Libya as a pointer to the scholarly written books in the area. Libya, as a matter of fact, does not confine itself to one particular school of law, rather, it counts much the validity and genuinety of evidence, even, if the evidence is in contradiction with the guidelines laid down by the Maliki school of Jurisprudence at it belongs to. We adopted in this work both Deductive and Descriptive methods of research. Lastly, we conclude this work with some suggestions to our fellow colleagues in research that, attention should be paid to newly topics and contemporary issues in libya .